English Characteristic Semantic Block Processing Based on English-Chinese Machine Translation - Yuxiu Yu (Advances in Multimedia)
In order to solve the problem that the current English-Chinese machine translation software cannot understand the characteristics of English sentences repeatedly, a semantic block processing method for English-Chinese machine translation was proposed. In the process of the English sentence comprehension, English semantic block, which played an important role, was analyzed in detail. On the basis of this, the core content and characteristics of English semantic block were discussed. And with the help of the corresponding processing algorithms, taking verbs and business English as the research object, three kinds of semantic models were summarized. A lexical chunk database model based on English characteristic semantic block processing was proposed. The open test results showed that the matching success rate of the model for the semantic pattern database was about 90%.